The role of Kurdish women in the field of science and enlightenment (7_9 AD /13_15 AD) - Mohammed, Dr. Mohsen Maml (Sulaimani Journal for Humanities, 2026)
Kurdish women have played an active role in Islamic society. Whenever they have the opportunity, they have used their abilities and played an active role in the development of society, especially in matters related to education and household chores. Despite being engaged in household chores, education and raising children, some Kurdish women have participated actively in all spheres of life alongside men, especially alongside scholars, jurists and scholars The most prominent teachers of the time. It is no exaggeration to say that some of the Kurdish women in the Kurdish cities of the Jazira region were at a high level of intellectual and enlightenment and had a good knowledge of Shari'ah sciences such as the Qur'an and Hadith They were intellectual and scientific and a large number of scientists and thinkers received scientific degrees on their hands.
Keywords: Al Jazeera Region; Kurdish Women; Quranic Science; Hadith Science; Scientific Certificate